IMPLEMENTASI PENGUAT JARINGAN POINT TO POINT POLITEKNIK NEGERI SRIWIJAYA KE AGROTEKNO DESA GELEBAK DALAM - Sarjana; Zefi, Susan; Damayanti, Cesha (JURNAL TELISKA, 2023)
In this research the author aims to increase and expand the coverage of the Wireless LAN connection signal at Sriwijaya State Polytechnic to Agrotekno Gelebak Dalam. The testing method used is to use the Ubiquiti AirOS PowerBeam M5 using Field Research and Literature Research methods for data collection methods and network testing guidelines. WLAN and the implementation of a WLAN network amplifier refers to the Wifi Range Extender or TP-Link TL WA855RE. In this research entitled Implementation of a Series of Point to Point Network Amplifiers at Sriwijaya State Polytechnic to Agrotekno Gelebak Dalam Village which refers to the method of Implementing a TP-Link TL WA855RE Network Amplifier So it can be concluded that strengthening the WLAN network by adding a Repeater or Wifi Range Extender is more efficient in saving time and costs in its implementation. Key words : WLAN, Implementation, Repeater